Knowledge and awareness of child sexual abuse related to POCSO (Protection of Children from Sexual Offences) Act among medical and dental professionals in India: A cross-sectional study - Upasana Tyagi; Vaibhav T. Chougule; Raghu Devanna; Rahul Kumar Anand; Noura Abdulaziz Alessa; Amol Jain; Nazargi Mahabob; Harshita Lath; Vijay Wadhwan (Journal of Family Medicine and Primary Care)
Background: The POCSO (Protection Of Children from Sexual Offences) Act was introduced in 2012 as a measure to safeguard and prevent interests of children affected by sexual crimes. Both medical and dental professionals are capable of identifying such cases. Aim: The aim of this study was to evaluate the knowledge and awareness of child sexual abuse related to POCSO Act among both medical and dental professionals in India. Materials and Methods: This cross-sectional questionnaire-based study was conducted on 100 medical and dental healthcare professionals employed in a single hospital for evaluation of knowledge and awareness on POCSO Act. The questionnaire containing multiple choice questions was randomly distributed among all the study participants as hard copy or via electronic generated forms. The questionnaire comprised questions related to demographics and those dealing with knowledge and attitude. Statistical Analysis: Categorical variables were represented in the form of percentages, and data analysis was done using SPSS software. Results: 67% study participants demonstrated full knowledge of POCSO, 23% had some knowledge, and 10% study subjects had absolutely no knowledge regarding this act. 7% professionals opined that the support for such affected children must come from Government Organizations, while 15% believed that Non-Governmental Organizations must support these children. 28% professionals believed that the child support and welfare committee should play a role in supporting these children. However, 50% study participants were of the opinion that the primary support must be community-based. On analyzing statistically, level of knowledge and awareness were found to be statistically significant (P = 0.05). Conclusion: There appears to be a good amount of knowledge and attitude among both medical and dental professionals regarding POCSO Act.